The Effect of GCG on Company Value With Financial Performance As An Intervening Variable - Sri TRISNANINGSIH; Bella Putri RAHMASARI (Journal of Tourism Economics and Policy, 2023)
This research has the main objective to determine the effect of good corporate governance (GCG) proxied by managerial ownership and institutional ownership on firm value proxied by PBV and through financial performance as an intervening variable proxied by ROA. Quantitative research is used in this research which has a population of 169 manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2019 period. The sample of this research was taken using purposive sampling, obtained 60 samples. The technical analysis used in this study is path analysis through IBM SPSS Statistics 25 software. This research shows that good corporate governance (GCG) is proxied through managerial ownership and institutional ownership has no effect on firm value (PBV), good corporate governance (GCG) is proxied through managerial ownership, and institutional ownership does not affect financial performance (ROA). Financial performance influences firm value (PBV), good corporate governance (GCG) is proxied through managerial ownership and institutional ownership influences firm value (PBV) through financial performance (ROA) as an intervening variable.